Little cicada of sugarcane Mahanarva posticata (Homoptera: Cercopidae). A Brazilian agricultural pest. Morpho-histological study of salivary glands - Roma, Gislaine Cristina [UNESP]; Camargo-Mathias, Maria Izabel [UNESP]; Arrigoni, Enrico de Beni; Marin-Morales, Maria Aparecida [UNESP] (International Society of Cytology, 2003)
Little cicadas are homopteran insect pests of sugarcane plantations. As these insects suck out the sap from the leaf parenchyma, they inoculate a toxic saliva that damages the plant vessels, thus promoting the loss of glucose by the affected plant. The morphological and histological analyses of the salivary glands of the little cicada Mahanarva posticata, revealed that these glands are formed by 2 portions: one portion comprises a group of acini and has been denominated as the principal gland; the second portion is filamentous in nature and has been denominated as the accessory gland; it is formed by very long and fine filaments. The acinous portion of the gland can be subdivided into 2 lobes: an anterior lobe formed by 3 lobules (I, II, III), and a posterior lobe formed by lobule IV and the excretory duct. Histologically, the salivary glands showed that the filaments are empty sutructures composed by several internal channels with secretion granules being observed in the cytoplasm of the cells of the secretory filaments. Lobules I and II of the principal gland are characterized by being highly basophilic and for accumulating a large amount of secretion in both the cytoplasm of the cells and inside secretion vesicles. Histochemically, we verified that the secretion produced by these glands is lipidic and protein in nature, with the production of polysaccharides being very low. The differences in stain and appearance of the different regions of the salivary gland lead us to believe that the final glandular product is lipoproteic in nature.
Keywords: Histochemistry; Histology; Little cicada of sugarcane; Mahanarva posticata; Salivary glands; Ultramorphology; Cercopidae; Cicada; Cicadidae; Hemiptera; Hexapoda; Insecta; Saccharum hybrid cultivar